2021
DOI: 10.1097/cce.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

ABCDEF Bundle and Supportive ICU Practices for Patients With Coronavirus Disease 2019 Infection: An International Point Prevalence Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 52 publications
6
45
1
3
Order By: Relevance
“…In addition, this bundle performance decreased the readmission to the ICU and discharge to a facility other than home [74]. However, the ABCDEF bundle was not sufficiently conducted in the COVID-19 pandemic with the bundle performance at A, 45%; B, 28%; C, 52%; D, 35%; E, 47%; and F, 16% [75]. These implementations were lower in the ICU where more beds were allocated for COVID-19 infections.…”
Section: Implementation Of the Abcdef Bundlementioning
confidence: 98%
See 2 more Smart Citations
“…In addition, this bundle performance decreased the readmission to the ICU and discharge to a facility other than home [74]. However, the ABCDEF bundle was not sufficiently conducted in the COVID-19 pandemic with the bundle performance at A, 45%; B, 28%; C, 52%; D, 35%; E, 47%; and F, 16% [75]. These implementations were lower in the ICU where more beds were allocated for COVID-19 infections.…”
Section: Implementation Of the Abcdef Bundlementioning
confidence: 98%
“…As a result, the frequency of unplanned extubations in COVID-19-infected patients was 13%, which is three times higher than other patients [81]. In this situation, physical restraints were reportedly used in 28% of mechanically ventilated patients [75]. A sedative in mechanically ventilated patients was excessively used with propofol 48%, dexmedetomidine 29%, and midazolam 7.7% [82].…”
Section: Analgesia Sedation and Delirium Carementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to direct structural changes being associated with delirium and other neurologic changes in patients with covid-19, patients with severe disease may receive deeper sedation, fewer breathing trials, and more limited mobility sessions than other critically ill patients. A worldwide two day prevalence study of ABCDEF* bundle practices across 212 ICUs in 38 countries found implementation rates to be low: pain assessment (45%), paired spontaneous awakening trial and spontaneous breathing trial (28%), sedation assessment (52%), delirium assessment (38%), early mobility and exercise (16% if patient being mechanically ventilated), and family engagement and empowerment (16%) 31. In the face of staggering numbers of critically ill patients with covid-19 met with an imbalance of staffing and resources to meet the demand,32 patients are unlikely to receive the usual quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…PICS is expected to be a major issue in the era of COVID-19, and the establishment of preventive measures through the surveillance of current situations is warranted [5,6]. Although evidence-based and supportive care in the ICU, such as the ABCDEF bundle, is expected to decrease PICS, a point prevalence study showed low implementation of the bundle [7]. The details of the long-term prognosis and PICS after COVID-19 infection have not been investigated in Japan.…”
Section: Introductionmentioning
confidence: 99%